Effect of Frozen Storage on the Physical Properties of Corrugated Fibre-Board Master Cartons and Waxed Duplex Cartons - GOPAL, T. K SRINIVASA; GOVINDAN, T K (Fishery Technology, 2017)
Deteriorative changes in physical properties of corrugated fibre-board mastercartons and waxed duplex cartons during frozen storage under commercial conditions were studied. Such changes due to prolonged exposure of these boards to moisture in the laboratory, effect of repeated wax-coating on the water resisting capacity of the boards and protection provided by increasing wax contents in the boards against water absorption and consequent deterioration in physical properties are reported.